(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2019)
The cession on well determined is a contract that has the purpose of transmitting the hereditary rights on a certain good. The object of the contract is hereditary rights, not things. The inheritance is a legal universality. The heir may dispose of his hereditary rights. If there is more than one heir with the death of a person, the state of hereditary indivision that extends to the partition and adjudication is born. Article 2309 of the Civil and Commercial Code of the Nation provides that the dispositions of the title referred to the transfer of inheritance are not applicable to the transfer of rights on specific property. The assignment of rights over a specific asset produces effects from its conclusion and legitimizes the transferee to claim the delivery of the thing or to be the successful bidder. Until the partition and or adjudication and the delivery of the thing the assignee does not hold a real right. The inscription in the Real Property Registry of the transfer of hereditary rights without a partitionand or adjudication is bad practice. It is necessary to review the customary practices and adapt them to the provisions of the current legal system.